Effect of the supporting zeolite structure on Cr biosorption: performance of a single-step reactor and of a sequential batch reactor: a comparison study - Figueiredo, Hugo (2010)
This work presents a study on the applicability of a zeolite-biomass system to the entrapment of metallic ions, starting from Cr(VI) solutions up to 100 mgCr/L, in batch processes. The effect of the zeolitic support on the overall system performance was evaluated comparing two large pore zeolitic structures which differ in chemical composition and ion-exchange capacity: Faujasite (HY and NaY) and Mordenite (HMOR and NaMOR) zeolites. The systems were tested in single-step and in sequential processes. In single-step studies, HY zeolite was found to be the most efficient support when applied to low Cr concentrations (overall Cr removal of 93.4%), whereas for the higher initial Cr concentration, the higher ion-exchange capacity of NaY zeolite was determinant to achieve the highest overall Cr removal of 77.6%. The evolution of Cr(VI) entrapment was strongly dependant on the zeolitic support used in the system. In sequential batch processes, HY zeolite was found to be the most efficient support with a 98.2% overall Cr removal. The reduction of Cr(VI) promoted by the biomass is more suited to the dynamics of the sequential process. NaY zeolite behaved similarly to HMOR and NaMOR zeolites, as these systems removed between 87.3 and 93.4% of the initial Cr.